The Affect The Effect Of Motoric, Sensoric And Cognitive On Speaking Ability Of Intellectual Disability Children - Sudarman Sudarman; Roy Romey Daulas Mangunsong (Poltekkes Kemenkes Surakarta, 2022)
Background: The growth and development of children is very important for parents to pay attention. The growth and development of children includes the development of motor, sensory and cognitive abilities. Normal sensory and cognitive motor abilities show maturity of brain function, but if there is a delay in motor, sensory and cognitive abilities, it can be caused by impaired brain function maturity, and this can occur in children with intellectual disabilities. Methods: This study applies a quantitative research with an observational analytic design through a cross sectional approach. The research sample was 50 respondents. Bivariate analysis using Spearman rank statistical test and multivariate analysis using multinomial logistic linear regression test model. Results: The results of Spearman's Rank analysis on motor development variables showed a p-value of 0.001 (p 0.05) and a correlation coefficient of 0.647 meaning that there was an effect. The results of the Spearman Rank analysis on the sensory development variable show a p value of 0.030 (p 0.05) and a correlation coefficient value of 0.738 which means there is an effect. The results of the Spearman Rank analysis on cognitive development variables show a p value of 0.003 (p 0.05) and a correlation coefficient of 0.455 which means there is an effect. The results of multivariate statistical tests using multinominal logistic regression analysis obtained a significance value of 0.005 (<0.05). Conclusion: The results of statistical tests with Spearmen Rank showed that sensory and cognitive motor development had an effect on the speech ability of ID children with a p value of 0.001; 0.30; 0.003 and the correlation coefficient value is 0.647; 0.738; 0.455. Meanwhile, the results of the multivariate test using logistic regression showed the value of sig. 0.005 < 0.05.